Evaluation of the Harmony of Trade Activities in the Letda Sujono Street Corridor Medan Tembung District Medan City - Trisilia Pohan; Feby Melanie; Abdi Sugiarto (International Journal of Society and Law, 2024)
The development of the population and its supporting facilities has an impact on improving the economy of the people of a city. The Jalan Letda Sujono corridor has experienced significant development of trade and service activities with the location of the area on the border of Medan City with Deli Serdang Regency and the access to the Bandar Selamat Toll Gate. The development of trade and service activities encourages the development of other activities such as housing, public services, commerce, warehousing and industry. This has a big impact on the demands of land provision, the potential for inconsistencies in the use of space, and the disruption of traffic circulation. Inconsistent land use is expected to affect the growth and development of the city which is irregular and directed (urban sprawl). The factor of incompatibility in space utilization in spatial planning is caused by the lack of effective control of space utilization. The Jalan Letda Sujono corridor is planned by the Medan City RDTR as a Trade Sub-Zone zoning which covers 3 (three) planned blocks and there are provisions for activities (zoning regulations) for several activities that are limited by a maximum proportion of 10% of the planned block area. For this reason, it is necessary to conduct a study of the suitability of existing activities with the zoning plan that has been stipulated in the Medan City RDTR as a content of space control in order to realize safe, comfortable and sustainable spatial arrangements. In this study, a qualitative descriptive method with a spatial analysis approach is used to be able to directly compare the existing activity map with the zoning map that has been determined in the Medan City RDTR. The analysis carried out was an analysis of the interpretation of existing activities using satellite images, an analysis of the conformity of the provisions of activities with spatial ovelaping, an analysis of the suitability of activities in excess of 10% proportion, and an analysis of the suitability of activities in the Trade Sub-Zone in the Letda Sujono Street Corridor. The results of this study show that there are 45 types of existing activities consisting of 6,403 persils of activities (polygons). The suitability of activities in the research area was 102.23 Ha (60.84%) and the non-conformity of activities was 65.80 Ha (39.16%). The Plan Block that has been exceeded by activities with a proportion of 10% is Block 17-07-01 (Tembung). In the Trade Sub-Zone in the corridor of Jalan Letda Sujono, it is known that the suitability of its activities covers an area of 19.45 Ha (89.05%) and the non-conformity of its activities covers an area of 2.39 Ha (10.95%). This indicates that the spatial zoning plan has not been fully realized with the existence of Unpermitted Activities (X) in the form of Integrated Schools and the existence of Conditional Activities (B) in the form of Vehicle Pools, Workshops, and Warehouses/Warehouses. The conditional activities are no longer allowed (not allowed) in the Plan Block 17-07-01 (Tembung) because it has exceeded the proportion of activities of 10% of the plan block.